Integration of Islamic Values in the Framework of Civilization: A Holistic Analysis of Law, Politics, Economics, and Socio-Culture - Setiawan, Asep (Proceedings: International Seminar On Educational Studies, 2025)
Islamic civilization is a unique civilization with integrative and interconnective characteristics between various aspects of life. This study aims to comprehensively analyze the integration of Islamic values in the four main pillars of civilization, namely: law (fiqh/sharia), politics (siyasah), economics (muamalah), and socio-culture. The research method used is descriptive-analytical qualitative with a library research approach that examines primary and secondary sources, including contemporary works by Muslim thinkers. The results of the study show that: (1) Islamic law based on Maqashid Sharia serves as a dynamic ethical-legal foundation; (2) The Islamic political system (Siyasah Syar’iyyah) functions as a dynamic ethical-legal foundation; (3) The Islamic economic system (Muamalah Syar’iyyah) functions as a dynamic ethical-legal foundation; and (4) The results of the research show that: (1) Islamic law based on Maqashid Sharia serves as a dynamic ethical-legal foundation; (2) The Islamic political system (Siyasah Syar’iyyah) emphasizes the principles of justice, deliberation (shura), and trust as instruments of governance; (3) Islamic economics offers an alternative paradigm of justice through the prohibition of usury, the application of zakat, and an emphasis on the real economy; and (4) Islamic socio-cultural values promote social cohesion based on ukhuwah (brotherhood), tolerance, and amar ma’ruf nahi munkar (enjoining what is good and forbidding what is evil). These four pillars are organically integrated into a solid civilizational structure. In conclusion, the integrative model of Islamic civilization is not only historically relevant, but also offers substantive solutions to various contemporary issues, such as inequality, ethical crises, and social disintegration. Collective ijtihad is needed to reactualize these values in the current context. Integration of Islamic Values, Islamic Civilization, Maqashid Syariah, Siyasah Syar’iyyah, Islamic Economics (Muamalah), Islamic Social Culture, Collective Ijtihad, Contemporary Solutions.